2014
DOI: 10.1177/0042098014542487
|View full text |Cite
|
Sign up to set email alerts
|

Contextual effects on educational attainment in individualised, scalable neighbourhoods: Differences across gender and social class

Abstract: This paper analyzes if a multi-scale representation of geographical context based on statistical aggregates computed for individualized neighborhoods can lead to improved estimates of neighborhood effect. Our study group consists of individuals born in 1980 that have lived in Sweden since 1995 and we analyze the effect of neighborhood context at age 15 on educational outcome at age 30 controlling for parental background. A new software, Equipop, was used to compute the socio-economic composition of neighborhoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 43 publications
3
92
0
1
Order By: Relevance
“…Taken together, the results from the OLS and the IV models, however, reveal some interesting and consistent patterns among these effects. In line with previous research (e. g., DeLuca et al 2012;Andersson & Malmberg 2013), heterogeneous effects for subgroups according to social status and sex were detected. Whereas the (modest) negative effect of an increasing share of high status neighbors for boys is also found in other studies (Orr et al 2003) and, in the present case, is more than merely cancelled out by the interaction effect for well integrated boys (-0.211 vs. 0.354), the differences across status groups need further attention.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Taken together, the results from the OLS and the IV models, however, reveal some interesting and consistent patterns among these effects. In line with previous research (e. g., DeLuca et al 2012;Andersson & Malmberg 2013), heterogeneous effects for subgroups according to social status and sex were detected. Whereas the (modest) negative effect of an increasing share of high status neighbors for boys is also found in other studies (Orr et al 2003) and, in the present case, is more than merely cancelled out by the interaction effect for well integrated boys (-0.211 vs. 0.354), the differences across status groups need further attention.…”
supporting
confidence: 91%
“…The relevant aspect of both, however, is the acceptance and internalization of these norms by the individual. As Crane (1991) as well as others (Andersson & Malmberg 2013;Sharkey & Faber 2014) have pointed out, such effects most likely differ according to the amount of disposable resources which may compensate for negative externalities (Greenman et al 2011) as well as according to sex, with boys usually being more impaired by worsen-ing neighborhood conditions than girls. But how do these norms spread through the neighborhood context?…”
Section: Epidemic Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…It is a typical observation in spatial context research that political borders are often not sufficient to define relevant areas (Hillmert 2015). In particular, research on the modifiable area unit problem (MAUP) has shown that the definition of areas affects the results, even when the same variables are analysed (Andersson and Malmberg 2014;Kwan 2012;Fotheringham and Wong 1991). As previous macro-level research suggest that regional training and labour markets differ in size, extension and accessibility, it is appropriate to include spatial measurements such as contiguities as well as commuting or travel time distances (e.g., Sforzi 2012;Heineck et al 2011;Eckey et al 2007).…”
Section: Hypothesis 1b: This Negative Impact Of Unemployment Is Highementioning
confidence: 99%
“…Andersson and Subramanian (2006) found very small effects of either parental or average neighbourhood income on length of education but both parents' education and proportion with higher education in the neighbourhood, as well as proportion receiving social assistance, had sizeable predictive power. Andersson and Malmberg (2015) report in a similar study that the strength of the estimated contextual effects increase substantially when statistics based on scalable individualized neighbourhoods are used to measure context. Several studies investigate educational achievements among immigrant children in Sweden.…”
Section: Families Neighbourhoods and Educational Outcomesmentioning
confidence: 95%